2017
DOI: 10.2174/1568026617666170504100642
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dopamine Signaling in Drug Addiction

Abstract: Addiction is a chronic, relapsing disease of the brain that includes drug-induced compulsive seeking behavior and consumption of drugs. Dopamine (DA) is considered to be critical in drug addiction due to reward mechanisms in the midbrain. In this article, we review the major animal models in addictive drug experiments in vivo and in vitro. We discuss the relevance of the structure and pharmacological function of DA receptors. To improve the understanding of the role of DA receptors in reward pathways, specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 0 publications
0
17
0
3
Order By: Relevance
“…Previous studies have consistently concluded that impulsivity was significantly associated with QOL, especially in a group of mental disorders characterized by impulsivity, such as bipolar disorder (9,22), attention deficit hyperactivity disorder (23,24) and emotional eating (25,26). In fact, although impulsivity has been shown to be a non-core symptom, in popular diagnostic systems (such as DSM-5 and ICD-11), certain impulsive behaviors can still be used to diagnose SUDs, such as uncontrolled drug seeking (27,28). Therefore, we hypothesized that the high impulsivity of patients with SUDs may have an impact on their QOL.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have consistently concluded that impulsivity was significantly associated with QOL, especially in a group of mental disorders characterized by impulsivity, such as bipolar disorder (9,22), attention deficit hyperactivity disorder (23,24) and emotional eating (25,26). In fact, although impulsivity has been shown to be a non-core symptom, in popular diagnostic systems (such as DSM-5 and ICD-11), certain impulsive behaviors can still be used to diagnose SUDs, such as uncontrolled drug seeking (27,28). Therefore, we hypothesized that the high impulsivity of patients with SUDs may have an impact on their QOL.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we concentrated on the relationship between DRD2 gene rs107656 and the personality traits measured with the Big Five Questionnaire (NEO-FFI), anxiety measured with the STAI to analyze the aspects modulating occurrence of substance dependence in the group of polysubstance-dependent patients. Dopamine is an essential factor in neural formation of a motivated behavior, and anomalies in the dopaminergic system seem to be essential elements in the etiology of motivation-related psychiatric disorders, mainly, dependence [37,38]. In our analysis, we observed that DRD2 rs1076560 variants influence the selected personality traits which are engaged in formation of a motivational behavior that can lead to dependence.…”
Section: Discussionmentioning
confidence: 63%
“…Such examples, at present, include drugs interacting with opioid receptors, CNS depressants (GABAA receptors); CNS stimulants (increased dopamine release/block re-uptake; nicotine), hallucinogens, glutamate antagonists (ketamine) and cannabinoids. 22,23 It seems reasonable that a molecule lacking CNS bioavailability would show a reduced likelihood of having a reinforcing property (e.g. loperamide 24 ), but now even large molecules are considered not to be excluded as having potential liability.…”
Section: Issues In Analgesic Drug Developmentmentioning
confidence: 99%